Effect of governance on deforestation a cross-country analysis - Legaspi, Arviel T.; Relampagos, Kaye Edson C.
Deforestation has wide-ranging impacts on environment, climate, biodiversity, economy, and human well-being. Studies have found several drivers of deforestation such as urbanization, population growth, and agricultural expansion. With this, governance has been recognized to play a key role in the management of forest resources, and ultimately, the reduction of rates of deforestation. This study provides empirical evidence on the role of the six dimensions of governance on deforestation rates across the world. By using data on deforestation, and the percentile ranking of 136 countries on the six World Governance Indicators, and employing two-step system-GMM, we found a statistically significant positive relation between all WGIs and deforestation rates for different periods across different countries. Our findings support the hypothesis that effective governance is necessary to maintain a sustainable use and management of forests. Thus, we conclude that addressing deforestation requires strong and effective governance systems that help promote sustainable forest management.